The Oxford handbook of innovation - Fagerberg, Jan.; Mowery, David C.; Nelson, Richard R. (Oxford handbooks in business and management., 2006)
This handbook provides academics and students with a comprehensive and holistic understanding of the phenomenon of innovation.